Young and old persons' subjective feelings when facing with a non-human computer-graphics-based agent's emotional responses in consideration of differences in emotion perception - Numata, Takashi; Asa, Yasuhiro; Hashimoto, Takaaki; Karasawa, Kaori (Frontiers in Computer Science, 2024)
Virtual agents (computer-graphics-based agents) have been developed for many purposes such as supporting the social life, mental care, education, and entertainment of both young and old people individuals. Promoting affective communication between young/old users and agents requires clarifying subjective feelings induced by an agent's expressions. However, an emotional response model of agents to induce positive feelings has not been fully understood due to differences in emotion perception between young and old adults. We investigated subjective feelings induced when facing with a non-human computer-graphics-based agent's emotional responses in consideration of differences of emotion perception between young adults and old adults. To emphasize the differences in emotion perception, the agent's expressions were developed by adopting exaggerated human expressions. The differences in their emotion perception of happy, sadness, and angry between young and old participants were then identified through a preliminary experiment. Considering the differences in emotion perception, induced feelings when facing with the agent's expressions were analyzed from the three types of emotion sources of the participant, agent, and other, which was defined as subject and responsibility of induced emotion. The subjective feelings were evaluated using a subjective rating task with 139 young and 211 old participants. The response of the agent that most induced positive feelings was happy when participants felt happy, and that was sad when participants felt sad, regardless emotion sources in both young and old groups. The response that most induced positive feelings was sad when participants felt angry and emotion sources were participant and the agent, and that was angry when the emotion source was other. The emotion types of the response to induce most positive feelings were the same between the young and old participants, and the way to induce most positive feelings was not always to mimic the emotional expressions, which is a typical tendency of human responses. These findings suggest that a common agent response model can be developed for young and old people by combining an emotional mimicry model with a response model to induce positive feelings in users and promote natural and affective communication, considering age characteristics of emotion perception.